PENGAWASAN IZIN PANGAN INDUSTRI RUMAH TANGGA OLEH DINAS KESEHATAN KOTA PEKANBARU (STUDI KASUS KECAMATAN SUKAJADI) - Erlinawati Hutapea; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Increased food industry followed by increasing demand for food products. The number of food products based on different types, shapes and flavors. Food products are needed by humans, therefore the need for continuous monitoring of the household food industry. Because the product of this household food industry is widely consumed. This supervision is carried out by Pekanbaru City Health Office to protect consumers to eat healthy, safe and decent food. The purpose of this study is to find out how Supervision of household food industry permits in Kecamatan Sukajadi and to determine what factors affect. This research is done by using qualitative research method. Data source is taken from primary and secondary data. In data collection, researchers used interview techniques, observation, and documentation. The informants were Pekanbaru City Health Office, Sukajadi District Business Owner, and Consumer, while the data analysis technique used was qualitative descriptive analysis. The results of this study indicate that the supervision conducted by Pekanbaru City Health Office has not been maximal, with the lack of guidance to business actors and unconfirmed punishment sanction, the lack of public participation in giving oral reports to Pekanbaru City Health Office, and the lack of awareness of home industry business owners ladder food against the prevailing regulations. Keywords: Supervision, Permit, Household Food Industry